2010
DOI: 10.3109/14992020903470809
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of noise-induced hearing loss in student musicians

Abstract: Abstract:This study describes the prevalence and characteristics of noise-induced hearing loss (NIHL) in student musicians (N = 329) aged 18-25 years. Students completed a questionnaire regarding exposures before a hearing assessment. NIHL was defined by the presence of a notch 15 dB in depth at 4000 or 6000 Hz relative to the best preceding threshold. Overall prevalence of NIHL was 45%, with 78% of notches occurring at 6000 Hz. The proportion of the total population with bilateral notching at any frequency wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 31 publications
(32 reference statements)
10
92
3
1
Order By: Relevance
“…The percentage of hearing disorders found in this study is similar to another analysis that assessed the hearing of percussionists, and found 39% of hearing loss and a higher proportion of hearing disorders when compared to the control group, which was equivalent in terms of gender and age (16) . In a study with 329 music students (aged between 18 and 25 years), there was no evidence of hearing loss, but of acoustic notch in 45% of the students (78% of them presented acoustic notch in 6,000 Hz and 22% in 4,000 Hz) (17) . Other studies also found hearing disorders among musicians, but not at high proportions; however, they observed acoustic notch in the frequencies of 4,000 or 6,000 Hz, more often than expected when compared to non-musicians, considering the same age and gender (1,3,8,9,(18)(19)(20) .…”
Section: Discussionmentioning
confidence: 95%
“…The percentage of hearing disorders found in this study is similar to another analysis that assessed the hearing of percussionists, and found 39% of hearing loss and a higher proportion of hearing disorders when compared to the control group, which was equivalent in terms of gender and age (16) . In a study with 329 music students (aged between 18 and 25 years), there was no evidence of hearing loss, but of acoustic notch in 45% of the students (78% of them presented acoustic notch in 6,000 Hz and 22% in 4,000 Hz) (17) . Other studies also found hearing disorders among musicians, but not at high proportions; however, they observed acoustic notch in the frequencies of 4,000 or 6,000 Hz, more often than expected when compared to non-musicians, considering the same age and gender (1,3,8,9,(18)(19)(20) .…”
Section: Discussionmentioning
confidence: 95%
“…Five papers considered high frequency tonal threshold, classifying mild hearing loss from 16dB and observed prevalence near 15% [24][25][26][27][28][29] . Four studies considered the mean of three frequencies (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, students had a high risk of excessive noise exposure from social and study-based music activities [Barlow 2010]. In another study, the prevalence of NIHL in 329 student musicians aged 18 to 25 years was 45% compared to 11.5% in the general population [Phillips et al 2010]. Although these studies surveyed undergraduate student musicians, many high school student musicians pursue musical study in college, attend loud concerts or nightclubs, and listen to loud music on personal music listening devices or stereos.…”
Section: Results and Discussion (Continued)mentioning
confidence: 99%